THE CULTIVATION OF ON A SUBSTRATE WITH BIRCH SAWDUST - Minakov D.V. (Техника и технология пищевых производств, 2016)
The use of wastes of hardwood trees growing on the territory of Russia for the cultivation of mushroom Grifola frondosa (Dicks: Fr.) is an actual problem. The aim of the research was to study the possibility of using birch sawdust as a substrate for growing mushroom cultures G. frondosa . The article presents the dependence of the substrate overgrowing degree on the cultivation time (twenty four hours). In 17 days of cultivation, the most rapid substrate overgrowth with mycelium occurred in samples no. 1 and no. 5. The relatively slow substrate overgrowth was fixed in samples no. 2, no. 3 and no. 4 in 23 days of cultivation. It has been shown that the productivity of mushroom biomass is increased by the enrichment of the substrate with additional components. It has been proposed to allocate three stages of G. frondosa maturity - biological, technical and complete. It has been established that mainly the fruit bodies of the first wave achieve the stages of complete technical maturity, while the appearance and the linear dimensions of mushroom of the second wave correspond to the stage of technical and biological maturity. The total mushroom yield depending on the substrate mass was 26.8%. It has been found that G. frondosa mushroom can give up to five waves of fruit bodies. Depending on the fruiting wave the mushroom yield for the first wave is 60%, for the second - 25%, for the third - 6.2%, for the fourth - 5.7%, for the fifth - 3.1%. The results obtained are of a practical value and contribute to the development of biotechnology and commodity science of the "Mushrooms" commodity group.